Evaluation de l’effet neurothérapeutique de la plante Anacyclus Pyrthrum L. sur la maladie d’Alzheimer (Etude in vivo) - Araya, Hadjar; Mostefa, Nadjet (My University, 2020)
Alzheimer's disease is a neurodegenerative disease that causes progressive and permanent deterioration of nerve cells resulting in a clinical picture of dementia. Herbal remedies are currently described as a promising source for identify new therapies. The aims of this study are to improve in vivo the neurotherapeutic effect of the aqueous extract of the roots of Anacyclus pyrethrum. The experimental protocol is established by two distinct periods; firstval is to induce Alzheimer's disease by oral administration of aluminum chloride (AlCl3) at 100 mg / kg combined with D-galactose at 120 mg / kg intraperitoneally for 45 days. Secondly represents the therapeutic period characterized by the administration of the extract of Anacyclus pyrethrum at 100 and 200 mg / kg by gastric tract during the 45 days which follow the reference retained in our study is Donepezil considered as an anti-Alzheimer’s. in the one handthe results of behavioral neurological tests reveal a less predominant state of anxiety in Alzheimer mice treated with the aqueous extract of PA at 200 mg / kg (Alz-D2) and 100 mg / kg (Alz-D1) compared to Alzheimer model mice (Alz-45J, Alz-90J) . on the other hand memory tests, demonstrate an improvement in learning ability and a remarkable recovery of memory in Alzheimer mice treated with aqueous extract of PA at 200 mg / kg (Alz-D2) compared to model mice Alzheimer's and Alzheimer's mice treated with Donepezil at 1 mg / kg (Alz-STD). To conclude, this present research allows us to confirm an additional neurotherapeutic activity of the roots of Anacyclus pyrethrum including antidepressant and nootropic properties.
Keywords: Alzheimer's; neurotherapeutics; Anacyclus pyrethrum L.; neurological tests; mice